Implementasi Kebijakan Pengembangan Pariwisata Di Provinsi Kalimantan Timur - Muhamad Japri; Sitti Aisyah; Ria Trisnomurti; Solikin (Collegium Studiosum Journal, 2020)
Tourism is a service trade industry that has a complex regulatory mechanism because it includes the arrangement of the movement of tourists from their home country to return to their home countries. To be able to achieve the success of tourism development, cross-sectoral support programs are required which is a program that is expected to be carried out by various agencies / other institutions that will help determine the success of cultural development and tourism. This study aims to (a) know and review the implementation of tourism development policy in East Kalimantan Province and (b) know and review the readiness of government officials in implementing the program. Research methods in the form of empirical legal research using primary and secondary data support and utilizing persuasive approaches in the form of interviews. The results show that the implementation of tourism development policy favors nature conservation and the strategies used in attracting tourists to East Kalimantan. Obstacles often faced by the East Kalimantan Provincial Government in implementing tourism development policies include the lack of seriousness of local and municipal governments to support the work programs of the Tourism Office.